2020
DOI: 10.1371/journal.pone.0234935
|View full text |Cite
|
Sign up to set email alerts
|

Association between admission systolic blood pressure and major adverse cardiovascular events in patients with acute myocardial infarction

Abstract: Background Several studies have previously demonstrated that higher systolic blood pressure level means lower risk of adverse cardiovascular outcomes. However, there is a lack of further investigation into the nonlinear relationship between admission systolic blood pressure (SBP) and adverse outcomes of acute myocardial infarction (AMI) patients. Objectives The aim of this study was to investigate the specific relationship between admission SBP and incidence of major adverse cardiovascular events (MACE) in 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…A number of studies have demonstrated an association between a lower incidence of MACE and higher SBP and DBP at admission [ 10 , 11 , 19 ]. In our cohort, both SBP and DBP were lower in the MACE group, and SBP at admission independently predicted in-hospital MACE.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated an association between a lower incidence of MACE and higher SBP and DBP at admission [ 10 , 11 , 19 ]. In our cohort, both SBP and DBP were lower in the MACE group, and SBP at admission independently predicted in-hospital MACE.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is the death or necrosis of myocardial cells caused by the occlusion of a coronary artery and is the most serious subtype of coronary heart disease [ 1 ]. In recent years, as AMI treatment options have improved, inpatient mortality rates have declined year on year, ranging from 2.5 to 8% [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is the most serious subtype of coronary heart disease. 1 According to NHANES data from 2013 to 2016, the overall prevalence of AMI among adults over 20 years old in the United States is 3.0%, and an American will suffer from AMI approximately every 40 s. 2 Moreover, the prognosis of AMI is poor, with a 5-year mortality rate as high as 51%, thereby heavily placing a huge health and socioeconomic burden. 3 Thus, risk factors of or models that can identify high-risk patients must be identified and developed to improve the prognosis of patients as timely and advanced interventions can administered.…”
Section: Introductionmentioning
confidence: 99%